On the overlap between apathy and depression in dementia. Issue 8 (15th July 2005) - Starkstein, S E; Ingram, L; Garau, M L; Mizrahi, R
Abstract : Background: Whereas apathy is increasingly recognised as a frequent abnormal behaviour in dementia, its overlap with depression remains poorly understood. Aims: To assess the psychometric characteristics of a structured interview for apathy, and to examine the overlap between apathy and depression in dementia. Methods: A total of 150 patients with Alzheimer's disease (AD) underwent a comprehensive psychiatric and cognitive assessment. Results: Twelve per cent of the sample met criteria for both apathy and depression, 7% met criteria for apathy only, and 31% met criteria for depression only. Apathy (but not depression) was significantly associated with more severe cognitive deficits. Apathy and anxiety scores accounted for 65% of the variance of depression scores in dementia, and the diagnosis of apathy had a minor impact on the rating of severity of depression. Conclusions: The Structured Interview for Apathy demonstrated adequate psychometric characteristics. Using a novel structured interview for apathy in AD we demonstrated that whereas the construct of depression primarily consists of symptom clusters of apathy and anxiety, apathy is a behavioural dimension independent of depression.